Knowledge, attitudes and practices on the use of household insecticide products: is the awareness in place? - Taib, Azratul Hizayu; Chen, Chee Dhang; Wahid, Noor Azrizal; Azirun, Mohd Sofian; Fong, Peng Chew; Low, Van Lun (Oxford University Press, 2021)
Insecticide application is one of the most important control measures for protection from mosquito bites. A descriptive, community-based cross-sectional survey involving 986 respondents was conducted to probe the knowledge, attitudes, and practices regarding household insecticide use in Selangor—the state that recorded the highest number of dengue cases in Malaysia. In this study, we classified the responses as either low (poor) or high (good) based on median cut-off points. Age, gender, ethnicity, and household income were found to be significantly associated factors relative to the respondents’ mosquito knowledge score, whereas no factors were significantly associated with attitudes toward the use of household insecticide. Practices, on the other hand, were associated with age and high attitude scores. Most respondents (71.4%) had good knowledge of mosquitoes. Conversely, 51.1% and 59.2% of respondents scored high on attitudes and practices, respectively, on the use of household insecticides. This study highlights the need to expand health promotion activities through social mobilization to raise awareness about vector-borne disease prevention and promoting positive attitudes and safe practices in the use of household insecticides.